Effect of milling time in production of urea compound by ball milling technique / Syasya Zulkipli - Zulkipli, Syasya (2018)
The study of the production of urea compound by ball milling technique gives the potential to solve the fertilizer problem. The aim of the paper was to investigate the optimum milling time in production of urea through ball milling techniques by varying the time taken for the tendency of urea to avoid become hygroscopic in order to generate quality urea fertilizer that will not cause hydrate formation in the presence of water that will make the mixture wet and sticky. Physical analysis showing that with prolonging the milling time, the mixture becoming from powder form to clumped. Through TGA, the influence of milling time and the content on the thermal stability of urea calcium phosphate has been investigated. The TGA analysis showing that weight loss increasing with increasing milling time up to 8 min, but showing weight loss starting from 10 min onwards. Weight loss showing the least at 2 min milling time. Through FTIR, the milling process of 2 minutes recorded moisture loss of 21.7% and 4.34 mg weight loss, while 4 minutes is at 24.01% with 4.80 mg, 6 minutes at 30.46% and 6.09 mg, 10 minutes is at 28.4% and 5.70 mg and 12 minutes at 25.28% and 5.06 mg of moisture loss and weight loss respectively for all of the samples that being milled. Through all the above characterizations of FTIR, XRD and TGA that has been made on milled urea calcium phosphate, optimum milling time in production of urea through ball milling techniques to avoid urea from becoming hygroscopic in order to generate quality urea fertilizer that will not cause hydrate formation in the presence of water that will make the mixture wet and sticky is at 2 min of milling. Physical analysis showing that with prolonging the milling time, the mixture becoming from powder form to clumped.